A randomised controlled trial of movement quality-focused exercise versus traditional resistance exercise for improving movement quality and physical performance in trained adults. Issue 24 (17th December 2019) - Bennett, Hunter; Arnold, John; Martin, Max; Norton, Kevin; Davison, Kade
ABSTRACT: The aim of this trial was to compare an eight-week individual movement quality versus traditional resistance training intervention on movement quality and physical performance. Forty-six trained adults were randomised to a movement quality-focused training (MQ) or a traditional resistance training (TRAD) group, and performed two individualised training sessions per week, for 8 weeks. Session-RPE (sRPE) was obtained from each session. Measures of movement quality (MovementSCREEN and Functional Movement Screen (FMS)) and physical performance were performed pre- and post-intervention. All measures improved significantly in both groups (3–14.5%, p = <0.005). The between-group difference in MovementSCREEN composite score was not statistically significant (0.3, 95% CI −3.4, 4.1, p = 0.852). However, change in FMS composite was significantly greater in MQ (1.3, 95% CI 0.8, 1.8, p < 0.001). There were no significant between-group differences in physical performance (p = 0.060–0.960). The mean sRPE was significantly lower in MQ (5.25, SD 1.2) compared to TRAD (6.6 SD 1.0, p = <0.001). Thus, although movement quality scores were not distinctly greater in the MQ group, a movement quality specific intervention caused comparable improvements in physical performance compared to traditional resistance training but at lower perceived training intensity.